Recent Progress on the Synthesis of Chiral Sulfones. Issue 5 (7th April 2021) - Huang, Youming; Li, Jinyao; Chen, Hongyi; He, Ze; Zeng, Qingle
Abstract: Chiral sulfones extensively exist in drugs, agricultural chemicals, chiral organic intermediates, and functional materials. Their importance causes the rapid development of their synthetic methods in recent years. Many transition metal complex catalysts with chiral ligands and chiral organocatalysts are adopted in synthesis of chiral sulfones. Most of the methods to construct chiral sulfones are based on the reduction of unsaturated sulfones and the introduction of sulfone groups into unsaturated hydrocarbons. This review describes all classes of asymmetric reactions for synthesis of chiral sulfones. Abstract : Because of the extensive bioactivities and excellent chiral induction ability of chiral sulfones, stereospecific synthesis of chiral sulfones are of great demand. This review comprehensively summarizes the recent progress in the synthesis of chiral sulfones.